Delayed replantation: Can it be a success? - Parolia, A; Kundabala, M; Shetty, N; Manuel, ST (Kathmandu University Medical Journal, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> This case report describes delayed replantation of an avulsed maxillary central incisor in a 17-year-old male patient following an injury on fall one day earlier. Avulsed maxillary right permanent central incisor was replanted back into the socket after extra-oral root canal treatment. One year follow up showed validity of treatment, with no evidence of resorption in the replanted tooth. Key words: Replantation, Maxillary central incisor, Resorption doi: 10.3126/kumj.v6i4.1742 Kathmandu University Medical Journal (2008), Vol. 6, No. 4, Issue 24, 497-501